You Shall Not Pass: Root Vacuoles as a Symplastic Checkpoint for Metal Translocation to Shoots and Possible Application to Grain Nutritional Quality - Ricachenevsky, Felipe K.; de Araújo Junior, Artur T.; Fett, Janette P.; Sperotto, Raul A. (Frontiers in Plant Science, 2018)
Plant nutrient uptake is performed mostly by roots, which have to acquire nutrients while avoiding excessive amounts of essential and toxic elements. Apoplastic barriers such as the casparian strip and suberin deposition block free diffusion from the rhizosphere into the xylem, making selective plasma membrane transporters able to control elemental influx into the root symplast, efflux into the xylem and therefore shoot translocation. Additionally, transporters localized to the tonoplast of root cells have been demonstrated to regulate the shoot ionome, and may be important for seed elemental translocation. Here we review the role of vacuolar transporters in the detoxification of elements such as zinc (Zn), manganese (Mn), cadmium (Cd), cobalt (Co) and nickel (Ni) that are co-transported with iron (Fe) during the Fe deficiency response in Arabidopsis thaliana, and the possible conservation of this mechanism in rice (Oryza sativa). We also discuss the evidence that vacuolar transporters are linked to natural variation in shoot ionome in Arabidopsis and rice, indicating that vacuolar storage might be amenable to genetic engineering without strong phenotypical changes. Finally, we discuss the possible use of root’s vacuolar transporters to increase the nutritional quality of crop grains.